Targeting time perception in biathlon: Examining physiological and perceptual responses to time pressure - Davis, P. A.; Åström, E.; McGawley, K.; Arnqvist, N. P.; Kårström, M. J. (Journal of Sports Sciences, 2026)
Performing under time pressure is critical, yet limited research has examined how psychophysiological and affective factors influence temporal estimation in sport competition. This study investigated the influence of psychophysiological exertion, fatigue, and affect on time perception during a simulated biathlon competition. Thirty-two biathletes (14 men, 18 women; age M = 21.3, SD = 3.9 y) completed five laps of roller-skiing separated by four shooting rounds (prone-standing-prone-standing). Prospective Time Production (PTP) and Prospective Verbal Estimation (PVE) were assessed alongside heart rate, perceived exertion, fatigue, and affective valence. Participants produced shorter intervals than the PTP target duration (29 s) post-competition (p < .001, d = 0.85), indicating time was perceived to pass faster relative to chronometric time under cumulative psychophysiological load. PVE accuracy differed by shooting position (p < .001, ?2 = .22), with time in prone perceived shorter than standing. Within-participant analyses showed higher heart rate, exertion, fatigue, and negative affect predicted greater temporal distortions during roller-skiing and shooting. These findings indicate that time perception in biathlon is dynamically shaped by interactions between physiological strain, affect, and task-specific attentional demands. Applied implications highlight integrating time perception calibration and affect regulation into pressure-training to improve pacing, shooting rhythm, and performance consistency.